Control of fluid intake by estrogens in the female rat: role of the hypothalamus - Santollo, Jessica; Daniels, Derek (Frontiers in Systems Neuroscience, 2015)
Body fluid homeostasis is maintained by a complex network of central and peripheral systems that regulate blood pressure, fluid and electrolyte excretion, and fluid intake. The behavioral components, which include well regulated water and saline intake, are influenced by a number of hormones and neuropeptides. Since the early 1970s, it has been known that the ovarian estrogens play an important role in regulating fluid intake in females by decreasing water and saline intake under a variety of hypovolemic conditions. Behavioral, electrophysiological, gene and protein expression studies have identified nuclei in the hypothalamus, along with nearby forebrain structures such as the subfornical organ (SFO), as sites of action involved in mediating these effects of estrogens and, importantly, all of these brain areas are rich with estrogen receptors (ERs). This review will discuss the multiple ER subtypes, found both in the cell nucleus and associated with the plasma membrane, that provide diversity in the mechanism through which estrogens can induce behavioral changes in fluid intake. We then focus on the relevant brain structures, hypothesized circuits, and various peptides, such as angiotensin, oxytocin, and vasopressin, implicated in the anti-dipsogenic and anti-natriorexigenic actions of the estrogens.